ANALISIS NILAI KARAKTER PROFIL PELAJAR PANCASILA BERGOTONG ROYONG DALAM FILM DENIAS SENANDUNG DI ATAS AWAN - Naufal Alif Firdaus; Ferina Agustini; Sunan Baedowi (STKIP Subang, 2023)
The purpose of this study is to describe the character values ​​of Pancasila student profiles as well as to analyze the character values ​​of Pancasila student profiles working together in the film Denias Senandung Di Atas Awan which can be applied to children. This research method is descriptive qualitative. This study uses data collection techniques in the form of interviews and observations. The results of the study show that there are a lot of Pancasila student profile character values ​​contained in the film Denias Senandung Di Atas Awan. The relevance of the character value of the Pancasila student profile of mutual cooperation contained in the film Denias Senandung Di Atas Awan with the character of the Pancasila student profile is the attitude of mutual cooperation which can be interpreted as an attitude or activity carried out by members of the community in cooperation and helping each other in completing work or problems with voluntarily without any reward so that the audience of this film can be instilled with this sense of mutual cooperation.